Biography of Sudarno Mahyudin as a writer from Riau (1960-2010) - Junianto, Wendi; Ahmal, Ahmal; Fikri, Asyrul (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
This research discusses the biography of Sudarno Mahyudin, who is a literary figure from Riau Province. The aim of this research is to determine Sudarno Mahyudin's life history, Sudarno Mahyudin's role as a writer, as well as Sudarno Mahyudin's works and achievements. This research uses a historical approach which includes heuristic, verification, interpretation and historiography stages. This research was conducted in Bagansiapiapi, Rokan Hilir Regency, Riau Province. The results of this research show that Sudarno Mahyudin was born in Bagansiapiapi on September 26 1940. Sudarno Mahyudin started school in 1947 at the Bagansiapiapi People's School and then continued his schooling on the island of Java at Surakarta Middle School in 1953-1956. After completing junior high school, he continued to Surakarta High School in 1956-1960. During high school, Sudarno Mahyudin began to enter the world of literature by filling in the sections for the wall magazine at his school. When he graduated from high school, in 1962 he continued to Gadjah Mada University (UGM) but did not finish in 1965. Thanks to his passion for writing, Sudarno Mahyudin plays a very important role in the world of literature, namely maintaining culture through literature, recalling history in Riau, creating the press media "Suara Rokan" in Bagansiapiapi, and creating the "Spirit Theater Studio". Sudarno Mahyudin has produced many works and has also received many awards at national and international levels.